Searching for Bright Lines in the Trump Presidency. Issue 3 (September 2019) - Carey, John M.; Helmke, Gretchen; Nyhan, Brendan; Sanders, Mitchell; Stokes, Susan
Abstract : Is American democracy under threat? The question is more prominent in political debate now than at any time in recent memory. However, it is also too blunt; there is widespread recognition that democracy is multifaceted and that backsliding, when it occurs, tends to be piecemeal. To address these concerns, we provide original data from surveys of political science experts and the public measuring the perceived importance and performance of U.S. democracy on a number of dimensions during the first year-and-a-half of the Trump presidency. We draw on a theory of how politicians may transgress limits on their authority and the conditions under which constraints are self-enforcing. We connect this theory to our survey data in an effort to identify potential areas of agreement—bright lines—among experts and the public about the most important democratic principles and whether they have been violated. Public and expert perceptions often differ on the importance of specific democratic principles. In addition, though our experts perceive substantial democratic erosion, particularly in areas related to checks and balances, polarization between Trump supporters and opponents undermines any social consensus recognizing these violations.